A brief screening measure for binge eating in primary care. (August 2017) - Dorflinger, Lindsey M.; Ruser, Christopher B.; Masheb, Robin M.
Abstract: Objective: Binge eating disorder (BED) is associated with medical and psychiatric issues commonly seen and managed in primary care; however, the disorder typically goes undetected as there are no assessment tools feasible for use in primary care. The objective was to examine the validity of the VA Binge Eating Screener (VA-BES), a single-item screening measure for binge eating. Method: The sample consisted of 116 veterans referred to a primary care-based weight management program. Participants had a mean age of 61.66 years ( SD = 8.73) and average BMI of 37.90 ( SD = 7.35). Frequency of binge eating ranged from zero to 21 episodes per week. The prevalence of BED was 7.76%. All participants completed the Questionnaire of Eating and Weight Patterns – Revised (QEWP-R) to assess for BED. They also completed the VA-BES, and measures of disordered eating and depressive symptoms. Results: The VA-BES was compared to the QEWP-R to determine the sensitivity, specificity, positive predictive value, and negative predictive value for each cutpoint. Analyses revealed one cutpoint (≥ 2 binge eating episodes per week) maximized these values, demonstrated excellent agreement with the QEWP-R (χ 2 = 24.79, p < 0.001), and had significant associations with other variables commonly associated with binge eating. Discussion: This study demonstrates the utility and validity of a single-item measure to screen for binge eating in primary care. The item can quickly and easily identify binge eating, thus facilitating referral to treatment and potentially subsequent improvements in related medical and mental health comorbidities treated in primary care. Highlights: Binge eating disorder (BED) can significantly impact medical and psychiatric issues. There are no tools that can feasibly be used to screen for BED in primary care. The VA Binge Eating Screener (VA-BES) is a single item measure of binge eating. The VA-BES demonstrates excellent sensitivity, specificity, and concurrent validity. The VA-BES can assist with screening and referral to treatment for BED.